Evaluation of tests based on the antibody response to keyhole limpet haemocyanin and soluble egg antigen to differentiate acute and chronic human schistosomiasis mansoni - Lílian Christina Nóbrega Holsbach Beck; Daniele S.M. Van-Lüme; Joelma Rodrigues de Souza; Clarice Neuenschwander Lins de Morais; Wlademir G Melo; Edeneide Maria Xavier; Constança Simões Barbosa; Marcílio L Aroucha; Ana Lúcia Coutinho Domingues; Tereza Cristina Favre; Otávio Sarmento Pieri; Frederico GC Abath; et al. (2004)
Specific IgG and IgM responses to soluble egg antigen (SEA) and keyhole limpet haemocyanin (KLH) were measured by ELISA in patients with acute and chronic schistosomiasis. The tests based upon IgM and IgG antibodies responses to KLH presented the best diagnostic discrimination, and can be used in conjunction with clinical and epidemiological data to the differential diagnosis of acute schistosomiasis.